Etanercept in Methotrexate-Resistant JIA-Related Uveitis. (January 2014) - Saeed, Muhammad Usman; Raza, Syed Hamid; Goyal, Sudeshna; Cleary, Gavin; Newman, William David; Chandna, Arvind
ABSTRACT We report our results with systemic Etanercept in patients with juvenile idiopathic arthritis in a joint ophthalmology–rheumatology clinic at a tertiary hospital. Methods: Patients with JIA on Etanercept were identified from a dedicated uveitis database. A retrospective review of electronic and paper-based patient records was performed. Results: Nine patients with JIA and current or previous treatment with Etanercept were identified, including six females and three males. Five patients with previous or current uveitis were noted. A further four were under observation for uveitis and required Etanercept for their joint disease. All nine patients had previously been taking Methotrexate, which had a suboptimal response in controlling arthritis or uveitis. Six out of nine patients did not show any uveitis activity at their last follow-up. Eyes of three patients still show signs of active inflammation in the anterior chamber (two on Etanercept and one off Etanercept). Severely impaired visual acuity (PL) was recorded in both eyes of one patient with long-standing persistent uveitis. Moderate visual loss in one eye of one patient was seen. The remaining seven patients did not show any significant loss of vision. Intraocular inflammation was not induced in any patient started on Etanercept. Conclusion: Etanercept may be useful in controlling JIA-related uveitis or arthritis in a pediatric patient when Methotrexate has had a suboptimal response in controlling the inflammatory activity.